The General Practitioner and the military veteran. Issue 2 (11th September 2014) - Simpson, Robin G; Leach, J
Abstract : Objectives: To assess the knowledge of members of the Royal College of General Practitioners (RCGP) on veteran's health issues, assess present support, and establish what support is required for GPs when treating veterans. Methods: An electronic survey of RCGP members across selected faculties. Results: Forty-seven per cent of respondents were 'unsure' or 'didn't know' how many veterans they were responsible for. However, many GPs replied that they had seen a veteran in the last month. Only 7.9% of respondents used the unique Read Code for veterans. Disappointingly, 75% of GPs indicated that they had not seen the RCGP leaflet on veterans' health, and less than 2% had used the RCGP On-Line e-learning resource. Conclusions: Surveyed GPs had little understanding of how many veterans were registered with their practice, and only a few had accessed learning resources available. GPs requested more information on how to assess veterans and where they could be referred. Further work is required to identify the true size of the problem, while continuing to provide proactive guidance and support to GPs on the health needs of veterans.